2021
DOI: 10.1021/acsnano.1c05685
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric Nanogenerator for Ocean Wave Graded Energy Harvesting and Condition Monitoring

Abstract: Using triboelectric nanogenerators (TENGs) to harvest blue energy in the ocean is advanced technology at present. In wave environments, the wave magnitude is constantly changing, so designing a TENG that can adjust the energy harvesting ability is necessary. Herein, a graded energy harvesting triboelectric nanogenerator (GEH-TENG) is fabricated, in which double generation units can operate in different transmission states to adapt to wave changes. Under small waves, the GEH-TENG is in the primary transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…[207] The method is based on triboelectric nanogenerator (TENG), combining electrostatic induction with contact-electrification and harvests energy from nature. [208][209][210][211][212][213][214][215] The polytetrafluoroethylene (PTFE) surface with a hierarchic nonwetting structure is used as a substrate. The system can output the electricity with 1.5 μA cm -2 current density and 20 mW cm -2 power density, driving 20 LEDs.…”
Section: Electricity Generationmentioning
confidence: 99%
“…[207] The method is based on triboelectric nanogenerator (TENG), combining electrostatic induction with contact-electrification and harvests energy from nature. [208][209][210][211][212][213][214][215] The polytetrafluoroethylene (PTFE) surface with a hierarchic nonwetting structure is used as a substrate. The system can output the electricity with 1.5 μA cm -2 current density and 20 mW cm -2 power density, driving 20 LEDs.…”
Section: Electricity Generationmentioning
confidence: 99%
“…(h) Ocean wave graded energy harvesting and condition monitoring with TENG (Reprinted with permission from ref. [295]. Copyright 2021 American Chemical Society).…”
Section: Blue Energymentioning
confidence: 99%
“…As shown in Figure 9g, Wang et al reported a flexible seaweed-like TENG (S-TENG) capable of harvesting wave energy when integrated into oceanographic buoys, undersea power stations, and coastlines [294]. Recently, as shown in Figure 9h, Xu et al reported a graded energy harvesting TENG (GEH-TENG) to adapt to changeable waves by two generation units operating in different transmission states [295]. Hence the GEH-TENG help monitor ocean wave condition and light caution lights installed on the shore.…”
Section: Blue Energymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] A graded energy harvesting triboelectric nanogenerator was proposed for ocean wave graded energy harvesting and condition monitoring by Xu et al. [ 36 ] Wang et al. designed sandwich‐like triboelectric nanogenerators for hydrodynamic parameters revealing and energy harvesting.…”
Section: Introductionmentioning
confidence: 99%